A Randomized Evaluation of a Computer-Based Nursing Documentation System - Ammenwerth, E.; Eichstädter, R.; Haux, R.; Pohl, U.; Rebel, S.; Ziegler, S. (Methods of Information in Medicine, 2001)
A two-month randomized, controlled trial based on 60 patients has been performed on a ward of the Department of Psychiatry at Heidelberg University Medical Center, Germany, to investigate the influence of computer-based nursing documentation on time investment for documentation, quality of documentation and user acceptance. Time measurements, questionnaires, documentation analysis and interviews were used to compare patients documented with the computer-based system (PIK group) with the control group (patients documented with the paper-based system). The results showed the advantages and disadvantages of computer-based nursing documentation. Time needed for nursing care planning was lower in the PIK group. Some formal aspects of quality were considerably better in the PIK group. On the other hand, time required for documentation of tasks and for report writing was greater in the PIK group. User acceptance increased significantly during the study. The interviews indicated a positive influence of PIK on the cooperation between nurses and physicians.
Keywords: Evaluation; Nursing Documentation System; Hospital Information System; Randomized Study